Encapsulation of the pulp of camu camu (Myciaria dubia) and dehydrated capsules - Terry Calderón, Víctor Manuel (2019)
The objective of this work was to study the formation of the pulp of camu camu in a matrix of calcium alginate encapsulation using the drip method by immersion of alginate solution of sodium, followed by a drying operation by dragging the process of external Gelation occurs with the calcium ion diffusion from a source that surrounds the hydrocolloid towards neutral pH alginate solution. Gel formation begins in the interface and moves inside to the surface is saturated with calcium ions, so that from the salt of alginate sodium ion is displaced by the Divalent cation solubilized in water. This interacts with the G- blocks of different polymer molecules, linking them together. Although, the most widely used source of calcium has been CaCl2 due to its higher percentage of available calcium, there are other salts employed less frequently such as acetate monohydrate and calcium lactate. Pulp of camu camu refined and at pH 3.3 neutralized with baking soda to pH 4.6 and using the direct gelling with sodium alginate in a proportion of 1g / 100 g and applying the drip technique in solution of 1g calcium chloride / 100g. And after several trials was the technique to produce areas of camu camu which were sifted and dried at a temperature of 60 °C resulting in 7, 40 g. / 100 g of pulp camu camu.